2016
DOI: 10.1093/cid/ciw076
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of a Low CD4/CD8 Ratio in HIV-1–Infected Individuals Despite Long-term Viral Suppression

Abstract: Most HIV-infected individuals with long-term viral suppression still had a CD4/CD8 ratio <1. Early initiation and long-term effective ART appear to improve this ratio. CMV coinfection, which represents a potential target for therapeutic intervention, was strongly associated with a persistently suboptimal CD4/CD8 ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
50
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 39 publications
4
50
0
1
Order By: Relevance
“…In the Italian cohort ICONA, the proportion of normalisation of CD4/CD8 ratio above 1 was 29.4% at 5 years of follow-up and an additional factor found associated with higher ratio was the lack of co-infection with cytomegalovirus (CMV) [17], a data that was not available in our cohort. Co-infection with CMV was also a determinant of a lower probability to reach a CD4/CD8 ratio above 1 in a transversal study conducted in Paris [18]. The mechanisms underlying the slow recovery of CD4/CD8 ratio despite the effectiveness of cART remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…In the Italian cohort ICONA, the proportion of normalisation of CD4/CD8 ratio above 1 was 29.4% at 5 years of follow-up and an additional factor found associated with higher ratio was the lack of co-infection with cytomegalovirus (CMV) [17], a data that was not available in our cohort. Co-infection with CMV was also a determinant of a lower probability to reach a CD4/CD8 ratio above 1 in a transversal study conducted in Paris [18]. The mechanisms underlying the slow recovery of CD4/CD8 ratio despite the effectiveness of cART remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Even in the setting of normal CD4 + counts among treated HIV-infected persons, low CD4/CD8 is associated with poor clinical outcomes [5,6], T-cell dysfunction [6][7][8], and increased inflammation (eg, interleukin 6, C-reactive protein, soluble CD14) [6,9]. These data suggest that CD8 + T-cell expansion might be a driver of increased morbidity and mortality [6,10].…”
mentioning
confidence: 99%
“…These bursts of replication are linked to persistent stimulation of the CD8 + T-cell population [13,14]. Along these lines, positive CMV serology among persons with chronic HIV infection is associated with lower CD4/CD8 ratio during ART [7]. A recent study found elevated CD8 + T cells and low CD4/CD8 only in individuals coinfected with both viruses, but not in persons infected with HIV or CMV alone [13].…”
mentioning
confidence: 99%
“…Our study has some limitations. First, we did not analyse variables related to reduced immunological recovery such as cytomegalovirus serology [5,34], but the double blind design of the study limits any bias in this sense. Second, this is a post-hoc analysis.…”
Section: Discussionmentioning
confidence: 99%